2005
DOI: 10.1111/j.1440-1630.2005.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of paediatric occupational therapy practice in Australia

Abstract: Background:The purpose of the present study was to describe a profile of Australian paediatric occupational therapy practice in terms of theories, assessments and interventions used with the most frequently seen client groups. Methods: An ex post facto survey design was utilised. A purpose-designed survey was mailed to 600 occupational therapists identified by OT Australia as working in paediatrics. Results: The response rate was 55% (n = 330). Respondents in the sample worked chiefly with children with develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 48 publications
3
80
0
2
Order By: Relevance
“…Development of the questionnaire was partially guided by previous surveys of practice patterns of occupational therapists with different patient populations (Koh, Hoffmann, Bennett & McKenna, 2009;McEneany, McKenna & Summerville, 2002;Rodger, Brown & Brown, 2005). Questions in section 1 used mainly fixed response category options asking about practice setting, caseload and length of time they had previously worked in dementia care.…”
Section: Measurementioning
confidence: 99%
“…Development of the questionnaire was partially guided by previous surveys of practice patterns of occupational therapists with different patient populations (Koh, Hoffmann, Bennett & McKenna, 2009;McEneany, McKenna & Summerville, 2002;Rodger, Brown & Brown, 2005). Questions in section 1 used mainly fixed response category options asking about practice setting, caseload and length of time they had previously worked in dementia care.…”
Section: Measurementioning
confidence: 99%
“…Surveys of pediatric therapists conducted in 2005 and 2008 indicated that NDT was commonly used in routine clinical practice (Rodger et al, 2005;Saleh et al, 2008). A more recent exploration of therapy management of upper limb dysfunction in children with CP highlighted approximately 90% of occupational therapists in the United Kingdom used NDT, 90% task practice, and 28% CIMT (McConnell et al, 2012).…”
mentioning
confidence: 99%
“…Performance-based tests are the most common type of pediatric motor skill assessment (Brown et al, 2007;Kramer et al, 2009;Rodger et al, 2005) and often follow a bottom-up approach, impairment focused assessment (Kennedy et al, 2013). Parent-report instruments of motor skill performance typically adopt a questionnaire-based format with items requiring Likert scale responses (Kennedy et al, 2013).…”
mentioning
confidence: 99%